Cinnamon Flour Enriched Commercial Feed (Burmese Cinnamon) With Different Dosage on the Growth of Cantang Group Fish (Ephinephelus Fuscoguttatus X Lanceolatus) - Syakirin, M. Bahrus; Soeprapto, Hayati; Mardianan, Tri Yusufi; Linayati, L; Aziz, Bagus Kuncoro (KnE Social Sciences, 2024)
The cantang grouper is the result of a cross between the tiger grouper and the kertang grouper (Ephinephelus fuscoguttatus x lanceolatus). It inhabits the bottom of tropical and subtropical sea waters, typically solitary, but forms groups when spawning, and is nocturnal. The selling price is quite expensive which makes it attractive. The purpose of this study was to determine the effect of adding cinnamon flour at different doses to commercial feed on the growth of cantang grouper. This study employed a quantitative experimental approach. The experimental design adopted was Completely Randomized Design (CRD), consisting of 4 treatments, each replicated 3 times. Parameters observed included Feed Conversion Ratio (FCR) value, the highest value was in treatment A and the lowest was in treatment B, namely in the treatment of giving cinnamon flour 0.5 g/100 g of feed. The survival rate of cantang grouper was notably high, with an average of 100% throughout the duration of the study. The addition of cinnamon powder in feed had a very significant effect on the growth of cantang grouper. The most substantial growth was observed in treatment B, where cinnamon powder was added at a rate of 0.5 g/100 g of feed, resulting in an average growth of 4.68 grams. The study of cantang grouper was supported by water quality parameters (DO, pH, turbidity, salinity), which remained conducive for the maintenance of cantang grouper juveniles. Keywords: cantang grouper, water quality, growth